MAKNA PROSESI PERKAWINAN JAWA TIMUR SEBAGAI KEARIFAN LOKAL (PENDEKATAN ETNOGRAFI KOMUNIKASI DALAM UPACARA TEBUS KEMBAR MAYANG DI DESA JATIBARU KECAMATAN BUNGARAYA KABUPATEN SIAK PROVINSI RIAU) - Usfatun Zannah; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Tebus kembar mayang ceremony is one of culture product. Nowadays, thisceremony is still running in village and done by community of east Java in jatibaruvillage bungaraya district siak regency as one of social culture.That activity includedvarious society (human) and as local genius.Inside of that ceremony occur socialinteraction between human, and this ceremony has symbolic meaning. The symbolicmeaning is a speech about truth of life for adult people who get marriage.Thisresearch focused by aim to know what the meaning procession marriage east java tosociety as local genius (approaching communication ethnography ceremony fromtebus kembar mayang in jatibaru village bungaraya district siak regency riauprovince). For answering the problem above, The writer take the reseach includephenomenology and symbolic interaction, in communication ethnography.This reseach approach is qualitative reseach with support by communicationethnography theory. The subject of this reseach is informant speaker that choosed bypurposive sampling technique consist of kembar mayang maker team, medicalpractisioner of meet wedding, family of female wedding, clergy and society whoinvolve in wedding party. The data of this reseach got from interview deeply,observation, documentation, library study and searching online data. For test of datavalidity used creadibilitas test . for technique of analysis data with redraw data,collecting data, serving data, take conclution and evaluation.Result of this reseach showed that tradition of tebus kembar mayangceremony not reputed only as tradition that exist in wedding party but tebus kembarmayang ceremony is a tradition that have values glorious and it will be given to twosubject of wedding in their new life at the future.